2022
DOI: 10.1017/dap.2022.2
|View full text |Cite
|
Sign up to set email alerts
|

Data responsibility, corporate social responsibility, and corporate digital responsibility

Abstract: This commentary looks at the use of corporate social responsibility (CSR) mechanisms for implementing responsible data use. The commentary offers an overview of CSR theory and the discourse on a growing phenomenon known as corporate digital responsibility (CDR). The commentary links these theories to the historical debates on the nature of technology, ethics, and society. The aim is to reflect on CSR and CDR mechanisms and ignite the discussion on their adequacy considering the pursuit of data responsibility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Some further areas of research can be identified that may help develop a broader picture of how CDR is being implemented. Van der Merwe and Al Achkar [7] (para. 25) recently suggested that CDR could be used for "whitewashing and regulatory capture".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some further areas of research can be identified that may help develop a broader picture of how CDR is being implemented. Van der Merwe and Al Achkar [7] (para. 25) recently suggested that CDR could be used for "whitewashing and regulatory capture".…”
Section: Discussionmentioning
confidence: 99%
“…CDR can be viewed as part of the wider concept of CSR, which has been recognised and reported upon in industry for several decades. Van der Merwe and Al Achkar [7] (p.4), for example, described CDR as "one part of an overall CSR model", but the focus on technology application and its repercussions warrants a clear distinction between the two concepts. Mihale-Wilson et al [8] (p.128) point this out thus: "due to the complexity that technology adds to corporate responsibility and the fact that managing the consequences and the opportunities that technologies can bring about requires a strong technological focus, it seems appropriate to view CDR as distinct from CSR."…”
Section: Relevant Literaturementioning
confidence: 99%
“…Two academic papers (Herden et al, 2021;Mueller, 2022) in our sample provided a summary of the CDR definitions (Table 4). Five other studies providing their own CDR definition were identified (Carl et al, 2022;Elliott et al, 2021;Trittin-Ulbrich and Böckel, 2022;Van der Merwe and Al Achkar, 2022;Wirtz et al, 2022).…”
Section: Cdr Definitions Overviewmentioning
confidence: 99%
“…Pelters (2021) define CDR as the voluntary incorporation of social and environmental considerations into a company's digital strategy, going beyond legal compliance to promote ethical and sustainable practices that generate broader societal, environmental, and economic benefits. Drawing on these perspectives, our paper proposes a comprehensive and holistic definition of CDR as the practices, policies, and governance structures organizations adopt during their digital transformation (Van der Merwe & Al Achkar, 2022). At the core of CDR lies the cultivation of responsible digital practices, the establishment of robust enforcement mechanisms, the pursuit of sustainable growth and development, and the fostering of trust within the digital ecosystem (Jelovac et al, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…These encompass (1) implementing digital security and consumer protection, (2) complying with legal and regulatory requirements, (3) analyzing to answer business questions, and (4) collaborating between employees. Regarding data security, the proliferation of digital services and the exponential growth of user information necessitate organizations' responsible handling and protection of data stored globally (Van der Merwe & Al Achkar, 2022). In digital responsibility, Mueller (2022) highlights that organizations must prioritize data privacy and security, as customers, employees, shareholders, regulatory authorities, and the public demand careful data management.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%